Edible Oil sebagai Pelarut Ekstraksi Karotenoid dari Kulit Labu Kuning (Cucurbita moschata) - Perwitasari Perwitasari; Heni Anggorowati; Susanti Rina Nugraheni; Indriana Lestari (Eksergi, 2023)
Carotenoids are pigments found in various types of fruits and vegetables that provide yellow, orange, and red colors. This study aimed to extract yellow pumpkin skin using edible oil solvents. The extraction process was carried out using ultrasound-assisted extraction (UAE) method with virgin coconut oil (VCO) and palm kernel oil (PKO). Yellow pumpkin peel powder with sizes of 40 mesh and 100 mesh were extracted with variations in extraction time (30 minutes, 60 minutes, and 90 minutes) and variations in solid-to-solvent ratio (1:10, 1:20, 1:30, 1:40, and 1:50). UV-Vis spectrophotometer analysis was used to determine the concentration of the extraction results. According to the research results, the best carotenoid concentration of 2513.44 ppm was obtained using PKO solvent with a powder size of 100 mesh, extraction time of 30 minutes, and powder-to-solvent ratio of 1:10.